Effects of Quercetin on Aspirin-Induced Haemato-Biochemical Alterations in Wistar Rats - Baraiya, Parth D; Patel, Jignesh M; Vihol, Priti D; Raval, Jitendra K; Parmar, Hitesh C; Patel, Sneha A; Panzade, Pranav R (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Aspirin is a non-steroidal anti-inflammatory drug (NSAID). Quercetin is natural flavonoid present in high concentration in herbal drugs, fruits and vegetables and demonstrating broad bio-pharmacological properties. This study was aimed to evaluate the ameliorative effects of quercetin (@ 100 & 200 mg/kg b.wt.) in aspirin (@ 100 mg/kg b.wt.) induced haemato- biochemical alterations in Wistar rats (n=36) over a period of 28 days. There was significant decrease in mean values of haemoglobin, packed cell volume, platelets and increase in total leucocyte count in aspirin treated rats (Gr. II) over the control group (Gr I) at 28th day of experiment. Similarly, in biochemical parameters also there was significant elevation in aspartate aminotransferase, alanine aminotransferase, urea and creatinine and significant decrease inmean values of total protein, albumin, triglyceride and cholesterol in aspirin treated rats. Administration of quercetin at higher dose rate of 200 mg/kg b.wt. for 28 days (Gr. III) along with the aspirin in Wistar rats prevented such alterations in different haemato-biochemical parameters as the values on day 28 were almost similar to those on day 0 and at par with control group. Hence, quercetin @ 200 mg/kg b.wt. along with aspirin @ 100 mg/kg b.wt. can be recommended to avoid aspirin induced health issues in high risk mammals.